2010
DOI: 10.1128/iai.01022-09
|View full text |Cite
|
Sign up to set email alerts
|

An Orally Applicable Shiga Toxin Neutralizer Functions in the Intestine To Inhibit the Intracellular Transport of the Toxin

Abstract: Shiga toxin 2 (Stx2) is a major virulence factor in infections with Stx-producing Escherichia coli (STEC), which causes gastrointestinal diseases and sometimes fatal systemic complications. Recently, we developed an oral Stx2 inhibitor known as Ac-PPP-tet that exhibits remarkable therapeutic potency in an STEC infection model. However, the precise mechanism underlying the in vivo therapeutic effects of Ac-PPP-tet is unknown. Here, we found that Ac-PPP-tet completely inhibited fluid accumulation in the rabbit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…Similarly, phase 1 clinical trials of chimeric monoclonal Stx1-and Stx2-neutralizing antibodies were also shown to be generally well tolerated in injected volunteers (383,384). Alternatively, short peptides may block Stx2 transport through epithelial cells (385). These cell-permeative peptides were also protective in a baboon model following Stx2 injection, as renal injury was abated (386).…”
Section: Clinical Considerationsmentioning
confidence: 92%
“…Similarly, phase 1 clinical trials of chimeric monoclonal Stx1-and Stx2-neutralizing antibodies were also shown to be generally well tolerated in injected volunteers (383,384). Alternatively, short peptides may block Stx2 transport through epithelial cells (385). These cell-permeative peptides were also protective in a baboon model following Stx2 injection, as renal injury was abated (386).…”
Section: Clinical Considerationsmentioning
confidence: 92%
“…To be successful such approaches have to overcome the millimolar intrinsic affinity for Gb 3 analogues and, at least for oligosaccharide based antagonists, the short half-life of such polar molecules in circulation. Several interesting approaches and ligand designs have been reported (22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Accordingly, several compounds with clustered trisaccharides that can bind to the B subunit with high affinity have been developed and shown to effectively neutralize Stx both in vitro and in vivo (27)(28)(29)(30)(31)(32)(33). These compounds, however, cannot be customized to specific Stx subtypes, because all Stx subtypes recognize the trisaccharide as the natural binding unit.Previously, we developed a library of multivalent peptides exhibiting the clustering effect, from which we identified Stx-neutralizing tetravalent peptides by screening the library for highaffinity binding to the specific receptor-binding sites (33)(34)(35)(36). By targeting Stx2a receptor-binding site 3 or Stx1a site 1, we identified various tetravalent peptides demonstrating remarkable therapeutic potency in both a mouse model of EHEC infection (34, 36) and a nonhuman primate model (19).…”
mentioning
confidence: 99%
“…Previously, we developed a library of multivalent peptides exhibiting the clustering effect, from which we identified Stx-neutralizing tetravalent peptides by screening the library for highaffinity binding to the specific receptor-binding sites (33)(34)(35)(36). By targeting Stx2a receptor-binding site 3 or Stx1a site 1, we identified various tetravalent peptides demonstrating remarkable therapeutic potency in both a mouse model of EHEC infection (34, 36) and a nonhuman primate model (19).…”
mentioning
confidence: 99%